DEVELOPMENT OF TEACHING MATERIALS BASED ON STEM EDUCATION TO IMPROVE STUDENT'S KNOWLEDGE, DATA LITERATURE, AND TECHNOLOGY - Vaizatul Uzfa; Asrizal Asrizal; Metta Liana (Universitas Negeri Padang, 2022)
In the 4.0 industrial revolution, it demands to have literacy skills in the 4.0 era which includes data literacy and technological literacy. There is STEM (Science, Technology, Engineering, Mathematics) education, students can improve skills in the fields of science, technology, engineering and mathematics in accordance with the demands of the industrial revolution 4.0. The purpose of this study was to determine the validity of STEM-based ICT-based teaching materials to improve students' data and technology literacy. This type of research is research and development. The instrument used in this study was a validity sheet. The results showed that the five assessment indicators had a validation value of 0.84 which were in the valid criteria. Therefore, STEM education ICT-based teaching materials to improve data literacy and technology are feasible to be used and tested for students.